2007
DOI: 10.1002/pola.22218
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and morphology of polyethylene chains grafted onto the surface of crosslinked polystyrene microspheres

Abstract: The bifunctional comonomer 4‐(3‐butenyl) styrene was used to synthesize crosslinked polystyrene microspheres (c‐PS) with pendant butenyl groups on their surface via suspension copolymerization. Polyethylene chains were grafted onto the surface of c‐PS microspheres (PS‐g‐PE) via ethylene copolymerizing with the pendant butenyl group on the surface of the c‐PS microspheres under the catalysis of metallocene catalyst. The composition and morphology of the PS‐g‐PE microspheres were characterized by means of Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Generally, control of the surface functionality of microspheres can be realized through two main approaches. The first one, especially for polymer microspheres, is to incorporate reactive block comonomers with desired functional groups into the polymer chains during the polymerization process 5. The presence of these reactive comonomers on microsphere surfaces can alter the surface characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, control of the surface functionality of microspheres can be realized through two main approaches. The first one, especially for polymer microspheres, is to incorporate reactive block comonomers with desired functional groups into the polymer chains during the polymerization process 5. The presence of these reactive comonomers on microsphere surfaces can alter the surface characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…However, ZrC σ‐bond could not be introduced using the reported supported catalysts, such as anchoring metallocene by methylaluminoxane (MAO) or surface covalently connected with ligands, or directly immobilizing by coordinative interaction . The previous studies have demonstrated copolymerization of vinyl groups linked to various substrates (silica,[10b],[10c], carbon nanotube, clay, alumina, or PS particles) with olefin monomers to introduce grafted polyolefin chain. With these vinyl‐substrates, we believe that a well‐known Schwartz hydrozirconation will probably provide a novel method for immobilization of zirconocene (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The first one, especially for polymer MSs, is to incorporate reactive block comonomers with desired functional groups into the polymer chains during the polymerization process. 22 The presence of these reactive comonomers on MS surfaces can alter the surface characteristics. Another commonly applied approach is chemical modification of the MS surfaces by a post-treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, control of the surface functionality of MSs can be realized through two main approaches. The first one, especially for polymer MSs, is to incorporate reactive block comonomers with desired functional groups into the polymer chains during the polymerization process . The presence of these reactive comonomers on MS surfaces can alter the surface characteristics.…”
Section: Introductionmentioning
confidence: 99%